Structural organization and phase behaviour of meta-substituted dioctadecylaminobenzoquinones at the air/water interface. Issue 5 (18th January 2019) - Behyan, Shirin; Gritzalis, Dimitrios; Schmidt, Rolf; Kebede, Eskedar; Cuccia, Louis A.; DeWolf, Christine
Abstract : A Langmuir monolayer formed from a zwitterionic lipid analogue that exhibits a highly reversible transition to a three-dimensional multilayer structure driven by headgroup crystallization. Abstract : The structural organization and phase behaviour of an amphiphilic zwitterionic quinonemonoimine at the air/water interface are presented. Brewster angle microscopy reveals multiple co-existing phases are observed over the entire isotherm while grazing incidence X-ray diffraction (GIXD) shows that these comprise both tilted, untilted and multilayer structures with crystalline headgroups. Despite the heterogeneity, the phase transitions are highly reversible over multiple cycles.